Concern About Abrupt Climate Changes Prompts Call for Early Warning System. (17th December 2013) - Showstack, Randy
Abstract : Abrupt changes in Earth's physical climate system—as well as abrupt impacts to physical, biological, or human systems from even gradual changes in the climate system—could lead to major disruptions, according to a report from the U.S. National Research Council (NRC) released on 3 December 2013. Moreover, there is an urgent need for an early warning system to better understand, anticipate, and prepare for those changes, the report states.